A simple intervention for disorders of consciousness- is there a light at the end of the tunnel? - Yelden, Kudret; James, Leon M.; Duport, Sophie; Kempny, Agnieszka; Farmer, Simon F.; Leff, Alex P.; Playford, E. Diane (Frontiers in Neurology, 2022)
Sleep is a physiological state necessary for memory processing, learning and brain plasticity. Patients with disorders of consciousness (DOC) show none or minimal sign of awareness of themselves or their environment but appear to have sleep-wake cycles. The aim of our study was to assess baseline circadian rhythms and sleep in patients with DOC; to optimize circadian rhythm using an intervention combining blue light, melatonin and caffeine, and to identify the impact of this intervention on brain function using event related potentials. We evaluated baseline circadian rhythms and sleep in 17 patients with DOC with 24-hour polysomnography (PSG) and 4-hourly saliva melatonin measurements for 48 hours. Ten of the 17 patients (5 female, age 30-71) were then treated for 5 weeks with melatonin each night and blue light and caffeine treatment in the mornings. Behavioural assessment of arousal and awareness (Coma recovery scale-revised (CRS-R)), 24-hour polysomnography and 4-hourly saliva melatonin measurements, oddball mismatch negativity (MMN) and subject’s own name (SON) experiments were performed twice at baseline and following intervention. Baseline sleep was abnormal in all patients. Cosinor analysis of saliva melatonin results revealed that averaged baseline % rhythmicity was low (M: 31%, Range: 13% - 66.4%, SD: 18.4). However, increase in %Melatonin Rhythm following intervention was statistically significant (p=0.012). 7 patients showed improvement of CRS-R scores with intervention and this was statistically significant (p=0.034). All the patients who had improvement of clinical scores also had statistically significant improvement of neurophysiological responses on MMN and SON experiments at group level (p=0.001). Our study shows that sleep and circadian rhythms are severely deranged in DOC but optimization is possible with melatonin, caffeine and blue light treatment. Clinical and physiological parameters improved with this simple and inexpensive intervention. Optimization of sleep and circadian rhythms should be integrated into rehabilitation programs for people with DOC.